Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor